Comparison of local influenza vaccine effectiveness using two methods. Issue 8 (22nd February 2021) - Balasubramani, G.K.; Zimmerman, Richard K; Eng, Heather; Lyons, Jason; Clarke, Lloyd; Nowalk, Mary Patricia
Highlights: Influenza vaccine effectiveness is typically estimated using the test negative design. Data for VE estimates may be derived from administrative or research databases. Comparing these data sources results in insignificant differences in VE estimates. Advantages of administrative databases are lower cost and potentially faster results. Advantages of research databases are less selection bias and more complete data. Abstract: Background: In some settings, research methods to determine influenza vaccine effectiveness (VE) may not be appropriate because of cost, time constraints, or other factors. Administrative database analysis of viral testing results and vaccination history may be a viable alternative. This study compared VE estimates from outpatient research and administrative databases. Methods: Using the test-negative, case-control design, data for 2017–2018 and 2018–2019 influenza seasons were collected using: 1) consent, specimen collection, RT-PCR testing and vaccine verification using multiple methods; and 2) an administrative database of outpatients with a clinical respiratory viral panel combined with electronic immunization records. Odds ratios for likelihood of influenza infection by vaccination status were calculated using multivariable logistic regression. VE = (1 − aOR) × 100. Results: Research participants were significantly younger ( P < 0.001), more often white (69% vs. 59%; P < 0.001) than non-white and less frequently enrolled through the emergency department (35% vs. 72%; P < 0.001) than administrative database participants. VE was significant against all influenza and influenza A in each season and both seasons combined (37–49%). Point estimate differences between methods were evident, with higher VE in the research database, but insignificant due to low sample sizes. When enrollment sites were separately analyzed, there were significant differences in VE estimates for all influenza (66% research vs. 46% administrative P < 0.001) and influenza A (67% research vs. 49% administrative; P < 0.001) in the emergency department. Conclusions: The selection of the appropriate method for determining influenza vaccine effectiveness depends on many factors, including sample size, subgroups of interest, etc., suggesting that research estimates may be more generalizable. Other advantages of research databases for VE estimates include lack of clinician-related selection bias for testing and less misclassification of vaccination status. The advantages of the administrative databases are potentially shorter time to VE results and lower cost.